Epidemiologic evaluation of pleurisy diagnosed by surgical pleural biopsy using data from a nationwide administrative database. Issue 8 (4th March 2022) - Hara, Kanako; Yamasaki, Kei; Tahara, Masahiro; Ikegami, Hiroaki; Nishida, Chinatsu; Muramutsu, Keiji; Fujino, Yoshihisa; Matsuda, Shinya; Fushimi, Kiyohide; Mukae, Hiroshi; Yatera, Kazuhiro
Abstract: Background: Pleural biopsies for investigating the causes of pleurisy are performed through modalities including needle biopsies, local anesthetic thoracoscopic procedures, and surgery (video‐assisted thoracoscopic surgery and open thoracotomy). To date, there have been no large‐scale nationwide epidemiological studies regarding pleurisy diagnosed via surgical pleural biopsy. This study examined the epidemiology of pleurisy diagnosed via surgical pleural biopsy in a Japanese nationwide administrative database. Methods: We evaluated Japanese Diagnosis Procedure Combination data of 24 173 patients who underwent video‐assisted thoracoscopic surgery or open thoracotomy and received a diagnosis of pleurisy between April 2014 and March 2020. In addition to pleurisy diagnoses, the patients' clinical information, including age, sex, smoking status (pack‐years), dyspnea grade, length of in‐hospital stay, and comorbidities, were extracted from the dataset. Results: This study included data from 1699 patients. The most frequent causes of pleurisy were neoplastic diseases (55.9%; malignant mesothelioma 22.5%, lung cancer 15.7%, lymphoma 2.5%), followed by infectious diseases (24.0%; tuberculosis 16.2%, parapneumonic pleural effusion 3.6%, empyema 3.5%, nontuberculous mycobacteriosis 0.5%), collagen vascular diseases (2.8%; rheumatoid arthritis 1.3%, immunoglobulin G4‐related diseases 0.7%, systemic lupus erythematosus 0.3%), and paragonimiasis (0.1%). Conclusions: Neoplastic diseases, including malignant mesothelioma and lung cancer, were frequently and accurately diagnosed as pleurisy via surgical pleural biopsy. The next leading cause was infectious diseases such as mycobacterial infections. Physicians should consider performing surgical biopsy in light of the knowledge regarding the etiology of pleurisy when a definitive diagnosis cannot be made via needle pleural biopsy. Abstract : This study evaluates data of epidemiology of pleurisy diagnosed via surgical pleural biopsy from a Japanese nationwide administrative database. This study includes data for 1699 patients. The most frequent causes of pleurisy are neoplastic diseases (55.9%): malignant mesothelioma 22.5%, lung cancer 15.7%, lymphoma, 2.5%. These causes also comprise infectious diseases (24.0%): tuberculosis 16.2%, parapneumonic pleural effusion 3.6%, empyema, 3.5%, nontuberculous mycobacteriosis 0.5%. Collagen vascular diseases (2.8%) and paragonimiasis (0.1%) are also etiologies of pleurisy.